Pain Mechanism in Rheumatoid Arthritis: From Cytokines to Central Sensitization - Yanting Cao; Danping Fan; Yiqing Yin (Hindawi Limited, 2020)
Pain is the most common symptom in patients with rheumatoid arthritis (RA). Although in recent years, through the implementation of targeted treatment and the introduction of disease-modifying antirheumatic drugs (DMARDs), the treatment of RA patients has made a significant progress, a large proportion of patients still feel pain. Finding appropriate treatment to alleviate the pain is very important for RA patients. Current research showed that, in addition to inflammation, RA pain involves peripheral sensitization and abnormalities in the central nervous system (CNS) pain regulatory mechanisms. This review summarized the literature on pain mechanisms of RA published in recent years. A better understanding of pain mechanisms will help to develop new analgesic targets and deploy new and existing therapies.